2002
DOI: 10.1093/cercor/12.4.395
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical, Physiological, Molecular and Circuit Properties of Nest Basket Cells in the Developing Somatosensory Cortex

Abstract: Anatomical, electrophysiological and molecular diversity of basket cell-like interneurons in layers II-IV of rat somatosensory cortex were studied using patch-clamp electrodes filled with biocytin. This multiparametric study shows that neocortical basket cells (BCs) are composed of three distinct subclasses: classical large (LBC) and small (SBC) basket cells and a third subclass, the nest basket cell (NBC). Anatomically, NBCs were distinct from LBCs and SBCs in that they formed simpler dendritic arbors and an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
317
5
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 348 publications
(348 citation statements)
references
References 58 publications
24
317
5
2
Order By: Relevance
“…For example, the firing of pyramidal cells in hippocampus is 1.4 Hz, whereas that of interneurons in the strata pyramidale and oriens is 15 Hz and 10 Hz, respectively. Similarly, cortical inhibitory interneurons may discharge 2-3 times faster than pyramidal cells 47 . In principle, inhibition may increase or decrease energy consumption depending on the contribution of the aforementioned factors (for a recent comprehensive review on inhibitory neurons and brain metabolism, see ref.…”
Section: Reviewsmentioning
confidence: 99%
“…For example, the firing of pyramidal cells in hippocampus is 1.4 Hz, whereas that of interneurons in the strata pyramidale and oriens is 15 Hz and 10 Hz, respectively. Similarly, cortical inhibitory interneurons may discharge 2-3 times faster than pyramidal cells 47 . In principle, inhibition may increase or decrease energy consumption depending on the contribution of the aforementioned factors (for a recent comprehensive review on inhibitory neurons and brain metabolism, see ref.…”
Section: Reviewsmentioning
confidence: 99%
“…A previous study in layer 4 of adult cat visual cortex found that up to 79% of basket cell inhibitory connections could be attributed to other basket cells . This finding was estimated based on the bouton size of anatomically identified interneuron synapses, likely including at least a large population of non-PV adapting nest and small basket cells within layer 4 (Dantzker and Callaway, 2000;Wang et al, 2002). Hence, differences in the interneuron populations, criteria for PV interneuron identification and the age and species of animals examined explain the discrepancies with our results.…”
Section: Layercontrasting
confidence: 70%
“…Fast-spiking PV cells of layer 4 are mostly large, nest, or clutch/small basket cells with axons and dendrites that ramify within their lamina of origin (Kisvarday et al, 1985;Wang et al, 2002). A noted exception are large basket cells whose axonal arbors can spread to lower layer 2/3 and layer 5/6 .…”
Section: Distinct Laminar Alterations Of Cortical Inhibitory Circuitrymentioning
confidence: 99%
See 2 more Smart Citations